KINERJA BIRO UMUM DAN KEUANGAN DALAM PENERIMAAN NEGARA BUKAN PAJAK DI UNIVERSITAS TADULAKO - Taswin, Taswin (Katalogis, 2015)
This study aims to determine the performance of General Affairs and Finance of the State Revenue Tadulako. The research method is qualitative research by selecting informants who can provide data according to the needs of research using Snowbaal. Data collection techniques in this study using the method: Observation (observation), interviews, and documentation. The results of the research showed that performance of General Affairs and Finance of the State Revenue Tadulako, has not gone well, because of the 5 indicators that were used in studying the problem of knife analysis research study found the facts that: 1) Productivity in non-tax revenue optimization can be said yet optimal due to non-tax revenue was only focused on the SPP funds. 2) The quality of service is already running optimally due to non-tax revenues was implemented by the University Tadulako with BLU system. 3) Responsiveness has not been optimal due to the asset management commitment Revenues Revenues Tadulako still weak, especially the aspect of control and monitoring of collaboration with the local government as Rusunawa Building for Students UNTAD. 4) The responsibility disenbabkan not yet optimal consistency setting time of receipt of non-tax revenues such as tuition payments, which often change - change, 5) Accountability is not running optimally due to frequent delays in reporting to the Ministry of Finance due to the delay of data units and existing faculty within the University Tadulako, due to the factor of human resources and inadequate infrastructure.